Penguins : Natural History and Conservation - Boersma, P. Dee, 1946-; Borboroglu, Pablo Garcia (Book collections on Project MUSE., 2016)
This timely book presents the most current knowledge on each of the eighteen penguin species - from the majestic emperor penguins of the Antarctic to the tiny blue penguins of New Zealand and Australia, from the northern rockhopper penguins of the South Atlantic and Indian oceans to the Galapagos penguins of the equator - written by the leading experts in the field.